2015
DOI: 10.1039/c5ta04008f
|View full text |Cite
|
Sign up to set email alerts
|

MnO2 nanoflake/polyaniline nanorod hybrid nanostructures on graphene paper for high-performance flexible supercapacitor electrodes

Abstract: A facile two-step strategy is adopted to construct free-standing composite paper of MnO2 nanoflakes/polyaniline (PANI) nanorods hybrid nanostructures on reduced graphene oxide (RGO) for flexible supercapacitor electrode application.MnO2 nanoflakes are firstly grown on RGO paper via electrodeposition method, followed by assembly of PANI nanorods between MnO2 nanoflakes by in situ polymerization using camphorsulfonic acid as dopant. The morphology and structure of composite paper are characterized and the electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(61 citation statements)
references
References 45 publications
3
57
1
Order By: Relevance
“…226.9 F g -1 and 162.9 F g -1 at 1 A g -1 , 2 A g -1 , 5 A g -1 and 10 A g -1 , respectively, the values are comparable to the previous studies, as shown in Table 1 [27][28][29][30][31][32][33][34][35]. Our 4-µm thick MCG flexible films with a packing density of 0.87 g cm -3 , which leads to a significant gravimetric capacitance of 277.8 F cm -3 , which is much higher than previously reports.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 92%
“…226.9 F g -1 and 162.9 F g -1 at 1 A g -1 , 2 A g -1 , 5 A g -1 and 10 A g -1 , respectively, the values are comparable to the previous studies, as shown in Table 1 [27][28][29][30][31][32][33][34][35]. Our 4-µm thick MCG flexible films with a packing density of 0.87 g cm -3 , which leads to a significant gravimetric capacitance of 277.8 F cm -3 , which is much higher than previously reports.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 92%
“…28,29 Numerous free-standing electrodes have been fabricated through mechanical mixing, chemical deposition or hydrothermal reaction of pseudocapacitive species with 2D flexible graphene. [30][31][32][33][34][35][36][37] These electrodes are generally consist of 5 pseudocapacitive components for high capacitance, and good ionic-electric conductive pathways for rapid ion diffusion and electron transport. 38,39 In addition, the electrodes are generally densely stacked without added binders and conductive additives, to achieving high volumetric capacitance.…”
mentioning
confidence: 99%
“…Both Co 3 O 4 and CoS are employed as active materials, while the conductive CC as a current collector guarantees effective ion and electron transport throughout the electrode [34]. …”
Section: Resultsmentioning
confidence: 99%